Integrated North American energy markets under different futures of cross-border energy infrastructure. (September 2020) - Siddiqui, Sauleh; Vaillancourt, Kathleen; Bahn, Olivier; Victor, Nadejda; Nichols, Christopher; Avraam, Charalampos; Brown, Maxwell
Abstract: We study how changes in cross-border energy infrastructure in North America will impact local and national markets. Electricity and natural gas are all transported across the borders of Canada, US, and Mexico. However, future changes in the energy production mix will lead to the further development of these infrastructures, as energy supply and demand cause stress across borders. We use a multimodel approach to investigate what happens to standard output metrics of local energy markets when these infrastructures are changed under different scenarios. These scenarios include increasing the capacity of electricity transmission by 20% and decreasing the cost of transporting natural gas by 20% vis-à-vis the modelers' reference case starting 2020. We find that electricity transmission across the Canadian-US border increases, with most of the increase in electricity production by natural gas. We also find that natural gas trade increases across the US-Mexico border, with a change in flows of natural gas within the US moving away from the northeast and northwest. While electricity production from renewable energy is expected to increase in the reference scenario, the changes in cross-border energy infrastructure do not significantly impact the generation from renewable energy. The scenarios help identify bottlenecks in the cross-border energy infrastructure, and propose future investment opportunities to decrease overall system costs for producing and consuming energy. Highlights: We study how cross-border energy infrastructure will impact regional markets. Electricity transmission across the Canadian-US border increases with infrastructure. Natural gas trade increases across the US-Mexico border increases with infrastructure. Flows of natural gas within the US move away from the northeast and northwest.